2020
DOI: 10.1136/bmjopen-2020-042029
|View full text |Cite
|
Sign up to set email alerts
|

Experience of fatigue and associated factors among adult people living with HIV attending ART clinic: a hospital-based cross-sectional study in Ethiopia

Abstract: ObjectiveThis study aimed to determine the prevalence of fatigue and the factors associated among adult people living with HIV attending antiretroviral therapy clinic in Gondar town, Ethiopia.DesignCross-sectional.SettingGovernmental health facility that provides HIV care in Gondar town.Outcome measureFatigue is defined by nine items version Fatigue Severity Scale.ParticipantsAdult (aged 18 and above) people living with HIV in Gondar town (n=392).ResultA total of 408 HIV seropositive adults were approached for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
3
1
0
2
Order By: Relevance
“…Lastly, there was a strong relationship between living alone and fatigue. This relationship was also found in a recent study among adult PLHIV in Ethiopia (Baye et al, 2020), and in the general case, marriage is found to have a protective effect on health and survival (Zhu & Gu, 2010), which supports our finding.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Lastly, there was a strong relationship between living alone and fatigue. This relationship was also found in a recent study among adult PLHIV in Ethiopia (Baye et al, 2020), and in the general case, marriage is found to have a protective effect on health and survival (Zhu & Gu, 2010), which supports our finding.…”
Section: Discussionsupporting
confidence: 93%
“…Mental distress, trouble sleeping, body pain, multimorbidity, and living alone were significant predictors of fatigue. Nearly a third of the participants reported symptoms of anxiety and depression, which mirrors previous findings (Barroso et al, 2010;Barroso & Voss, 2013;Baye et al, 2020;Gebreyesus et al, 2020;Jong et al, 2010;Noh et al, 2012;Rodkjaer et al, 2010). Thus, it seems that identifying and treating depression are important when assessing fatigue treatment strategies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Проте дані про взаємозв'язок між втомою та кількістю Т-клітин CD4 +, вірусними навантаженнями ВІЛ та терапією АРТ суперечливі [11]. Деякі дослідники повідомляють про взаємозв'язок між високим рівнем вірусного навантаження ВІЛ, низьким рівнем вмісту Т-клітин CD4+ та підвищеною втомою, тоді як інші дослідники виявили, що втома є постійним симптомом незалежно від прогресування ВІЛ-інфекції або лікування [12]. На думку Barosso [13], втома тісно пов'язана з безсонням і порушенням фаз сну, характерних для ЛЖВ.…”
unclassified
“…Отже, фактори, які впливають на втому у ЛЖВ, а також методи її лікування, корекції та реабілітації, залишаються невирішеними питаннями охорони здоров'я [14]. Продовжуються дослідження з метою виявлення біомаркерів та інших фізіологічних корелятів, пов'язаних із втомою у ЛЖВ [11,12,14].…”
unclassified